Rates of convergence to equilibrium for collisionless kinetic equations in slab geometry - Mokhtar-Kharroubi, M; Seifert, D (Elsevier, 2018)
This work deals with free transport equations with partly diffuse stochastic boundary operators in slab geometry. Such equations are governed by stochastic semigroups in L1 spaces. We prove convergence to equilibrium at the rate O (t k/2(k+1)+1) (t -> +1) for L1 initial data g in a suitable subspace of the domain of the generator T where k 2 N depends on the properties of the boundary operators near the tangential velocities to the slab. This result is derived from a quantified version of Ingham’s taube- rian theorem by showing that Fg(s) := lim"!0+ (is + " − T )−1 g exists as a Ck function on R\ {0} such that dj/dsj Fg(s) ≤ C|s|2(j+1) near s = 0 and bounded as |s| ! 1 (0 ≤ j ≤ k) . Various preliminary results of inde- pendent interest are given and some related open problems are pointed out.